2015
DOI: 10.1007/s11883-015-0529-2
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Carotid Ultrasound Atherosclerotic Tissue Characterization and Stroke Risk Stratification in Machine Learning Framework

Abstract: Cardiovascular diseases (including stroke and heart attack) are identified as the leading cause of death in today's world. However, very little is understood about the arterial mechanics of plaque buildup, arterial fibrous cap rupture, and the role of abnormalities of the vasa vasorum. Recently, ultrasonic echogenicity characteristics and morphological characterization of carotid plaque types have been shown to have clinical utility in classification of stroke risks. Furthermore, this characterization supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…A disadvantage, however, is their inability to provide a “risk assessment.” The application of artificial intelligence (AI) can enhance the information provided by these imaging modalities, resulting in a more accurate characterization of the tissue and the disease process [ [45] , [46] , [47] , [48] , [49] , [50] , [51] ]. The combination of AI and medical imaging has been shown to improve diagnosis and risk stratification, speed up patient evaluation, enhance disease monitoring, and accelerate early intervention [ 40 , 48 , [52] , [53] , [54] , [55] , [56] , [57] ]. Thus, this review will focus on the use of AI-based tissue characterization of images of comorbid patients affected by COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…A disadvantage, however, is their inability to provide a “risk assessment.” The application of artificial intelligence (AI) can enhance the information provided by these imaging modalities, resulting in a more accurate characterization of the tissue and the disease process [ [45] , [46] , [47] , [48] , [49] , [50] , [51] ]. The combination of AI and medical imaging has been shown to improve diagnosis and risk stratification, speed up patient evaluation, enhance disease monitoring, and accelerate early intervention [ 40 , 48 , [52] , [53] , [54] , [55] , [56] , [57] ]. Thus, this review will focus on the use of AI-based tissue characterization of images of comorbid patients affected by COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Current systems are not fully automated 30 and lack advanced image-based features for risk assessment. 31,32 Often, these systems lack reliability, accuracy, reproducibility, and provide no comparative reference marker needed for monitoring. Furthermore, there is no standardization towards clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ultrasonic tissue characterization of carotid plaque has been also used in improving the prediction of coronary artery disease (CAD) events [28]. Furthermore several studies have shown that the presence of carotid plaque is better than that of carotid IMT for predicting future cardiovascular events [20,29,30].…”
Section: Discussionmentioning
confidence: 99%